Institutional delivery service utilization in Munisa Woreda, South East Ethiopia: a community based cross-sectional study - Amano Abdella; Gebeyehu Abebaw; Birhanu Zelalem (BMC, 2012)
Abstract Background Reducing maternal morbidity and mortality is a global priority which is particularly relevant to developing countries like Ethiopia. One of the key strategies for reducing maternal morbidity and mortality is increasing institutional delivery service utilization of mothers under the care of skilled birth attendants. The aim of this study was to determine the level of institutional delivery service utilization and associated factors. Methods A community-based cross-sectional survey was conducted from April 1-20, 2011, among mothers who gave birth 12 months before the study began in Munesa Woreda, Arsi Zone, Oromia Region, Southeast Ethiopia. A stratified cluster sampling was used to select a sample of 855 participants. Results Out of all deliveries, only 12.3% took place at health facilities. Women who were urban residents (AOR = 2.27, 95%CI: 1.17, 4.40), women of age at interview less than 20 years (AOR = 6.06, 95%CI: 1.54, 23.78), women with first pregnancy (AOR = 2.41, 95%CI: 1.17, 4.97) and, women who had ANC visit during the last pregnancy (AOR = 4.18, 95%CI: 2.54, 6.89) were more likely to deliver at health institutions. Secondary and above level of mother`s and husband`s education had also a significant effect on health institution delivery with AOR = 4.31 (95%CI: 1.62, 11.46) and AOR = 2.77 (95%CI: 1.07, 7.19) respectively. Conclusion Institutional delivery service utilization was found to be low in the study area. Secondary and above level of mother`s and husband`s education, urban residence and ANC visit were amongst the main factors that had an influence on health institution delivery. Increasing the awareness of mothers and their partners about the benefits of institutional delivery services are recommended.